2016
DOI: 10.1371/journal.pone.0149914
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Susceptibility in Chlamydia suis Pig Isolates

Abstract: The aims of the present study were to assess the prevalence of Chlamydia suis in an Italian pig herd, determine the tetracycline susceptibility of C. suis isolates, and evaluate tet(C) and tetR(C) gene expression. Conjunctival swabs from 20 pigs were tested for C. suis by real-time polymerase chain reaction, and 55% (11) were positive. C. suis was then isolated from 11 conjunctival swabs resampled from the same herd. All positive samples and isolates were positive for the tet(C) resistance gene. The in vitro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 14 publications
5
16
0
Order By: Relevance
“…We found that 1) the estimated number of gene copies in a clinical sample by real-time PCR is a good predictor to assess successful isolation, and 2) isolation from conjunctival swabs is far less successful compared to fecal samples suggesting that fecal contamination rather than actual conjunctival infection occurred. A selection of isolates (n = 59) were further tested for tet (C) by PCR as well as their antibiotic susceptibility in vitro , confirming previous findings that positive tet (C) results do not necessarily mean that the isolate is also phenotypically resistant [11]. Furthermore, we show that the number of tetracycline resistant C .…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…We found that 1) the estimated number of gene copies in a clinical sample by real-time PCR is a good predictor to assess successful isolation, and 2) isolation from conjunctival swabs is far less successful compared to fecal samples suggesting that fecal contamination rather than actual conjunctival infection occurred. A selection of isolates (n = 59) were further tested for tet (C) by PCR as well as their antibiotic susceptibility in vitro , confirming previous findings that positive tet (C) results do not necessarily mean that the isolate is also phenotypically resistant [11]. Furthermore, we show that the number of tetracycline resistant C .…”
Section: Introductionsupporting
confidence: 82%
“…For analysis, the number of inclusions at 200-fold magnification throughout the entire coverslip was counted and used to determine the number of inclusion-forming units per milliliter (IFU/ml). Each antibiotic susceptibility determination was performed with approximately 5 x 10 3 IFU/ml per investigated isolate as previously described [11]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular interest is the emergence of tetracycline resistance in C. suis, a growing problem in the pig rearing industry and probably the result of excessive tetracycline use for therapeutic purposes and as growth promoters in livestock since the 1950s (7)(8)(9)(10)(11). C. suis is primarily known to inapparently infect the porcine gastrointestinal tract with a prevalence of up to 90 % in fattening pigs (12).…”
Section: Introductionmentioning
confidence: 99%